The Paradigm of Differentiated Islamic Learning in Responding to Student Diversity - Fenti Tsuwaibatul Aslamiyah; Asmaji Muchtar; Toha Maksun (International Tatho Academics, 2025)
The diversity of conditions and needs of students in understanding teaching material is a challenge for educators to be able to implement accommodative learning strategies. This qualitative research in the form of a case study aims to describe the strategies and supporting factors related to differentiated learning in Akidah Akhlak subjects at Madrasah Aliyah Salafiyah (MAS) Yapensa Pekalongan City. Data were obtained through documentation, observation and interview techniques. Data analysis uses reduction, presentation, and conclusion drawing. The results showed that the differentiation learning strategy in the Akidah Akhlak subject at MAS Yapensa was effective. Through this strategy, the delivery of Akidah Akhlak material is carried out using various methods, such as the use of visual and audio media, and activities that involve motor skills. Meanwhile, there are supporting factors for the strategy, including the existence of training and professional development for teachers, teachers' skills and concern in moral education, policies and support from Madrasah, and the participation of parents. This research contributes to the importance of creative, contextual, and accommodating learning strategies amidst the diversity of learners' conditions and needs